Inverse Of Quadratic Functions

Examples, with detailed solutions, on how to find the inverse of quadratic functions with restricted domain are presented.

Example 1: Find the inverse of the quadratic function in vertex form given by

f(x) = 2(x - 2) 2 + 3 , for x <= 2

Solution to example 1:

  • Note that the above function is a quadratic function with restricted domain. Its graph below
    graph of quadratic function with restricted domain, example 1
    shows that it is a one to one function.Write the function as an equation.


y = 2(x - 2)
2 + 3

  • Solve the above for x to obtain 2 solutions

    (x - 2) 2 = (y - 3) / 2

    x - 2 = + or - sqrt[ (y - 3)/2 ]

    x = 2 + sqrt[ (y - 3)/2 ]

    and

    x = 2 - sqrt[ (y - 3)/2 ]

  • Since x given by x = 2 - sqrt[ (y - 3)/2 ] is always less than or equal to 2, we take the solution.

    x = 2 - sqrt[ (y - 3)/2 ]

  • Change x into y and y into x to obtain the inverse function.

    y = 2 - sqrt[ (x - 3)/2 ]

    f -1(x) = 2 - sqrt[ (x - 3)/2 ]

  • Example 2: Find the inverse of the quadratic function given by

    f(x) = -2 x 2 + 4 x + 2 , for x >= 1

    Solution to example 2:

    • We first need to show that this function is a one to one. Write f in vertex form by completing the square.

      f(x) = -2 (x 2 - 2 x) + 2 , for x >= 1

      f(x) = -2 (x 2 - 2 x + 1 - 1) + 2 , for x >= 1

      f(x) = -2 (x - 1) 2 + 4 , for x >= 1

      graph of quadratic function with restricted domain, example 2


    • The graph above is that of f and according to the horizontal line test f is a one to one function and therefore has an inverse.

    • Find the inverse of f, write f as an equation and solve for x. y = -2 (x - 1) 2 + 4

      x - 1 = + or - sqrt[ (y - 4)/- 2 ]

      x = 1 + sqrt[ (y - 4)/- 2 ]

      and

      x = 1 - sqrt[ (y - 4)/- 2 ]

    • Since x given by x = 1 + sqrt[ (y - 4)/- 2 ] is always greater than or equal to 1, we take the solution.

      x = 1 + sqrt[ (y - 4)/- 2 ]

    • Change x into y and y into x to obtain the inverse function.

      y = 1 + sqrt[ (x - 4)/- 2 ]

      f -1(x) = 1 + sqrt[ (x - 4)/- 2 ]




    Exercises: Find the inverse of the quadratic functions given below

    1. f(x) = (x - 3) 2 + 3 , if x >= 3

    2. g(x) = -x 2 + 4 x - 4 , if x <= 2


    Answers to above exercises:

    1. f -1(x) = 3 + sqrt[ (x - 3) ]

    2. g -1(x) = 2 - sqrt[ (-x) ]

    More links and references related to the inverse functions.



    Find the Inverse Functions - Calculator

    Find inverse of exponential functions

    Applications and Use of the Inverse Functions

    Find the Inverse Function - Questions

    Find the Inverse Function (1) - Tutorial.

    Definition of the Inverse Function - Interactive Tutorial

    Find Inverse Of Cube Root Functions.

    Find Inverse Of Square Root Functions.

    Find Inverse Of Logarithmic Functions.

    Find Inverse Of Exponential Functions.



    Home Page -- HTML5 Math Applets for Mobile Learning -- Math Formulas for Mobile Learning -- Algebra Questions -- Math Worksheets -- Free Compass Math tests Practice
    Free Practice for SAT, ACT Math tests -- GRE practice -- GMAT practice Precalculus Tutorials -- Precalculus Questions and Problems -- Precalculus Applets -- Equations, Systems and Inequalities -- Online Calculators -- Graphing -- Trigonometry -- Trigonometry Worsheets -- Geometry Tutorials -- Geometry Calculators -- Geometry Worksheets -- Calculus Tutorials -- Calculus Questions -- Calculus Worksheets -- Applied Math -- Antennas -- Math Software -- Elementary Statistics High School Math -- Middle School Math -- Primary Math
    Math Videos From Analyzemath
    Author - e-mail


    Updated: 2 April 2013

    Copyright 2003 - 2014 - All rights reserved